Antihypertensive drug reduction for treated hypertensive patients during the summer - Kimika Arakawa; Ai Ibaraki; Yuki Kawamoto; Mitsuhiro Tominaga; Takuya Tsuchihashi (Clinical and Experimental Hypertension, 2019)
Seasonal winter–summer variation in blood pressure (BP) has been reported, but there are few reports on the reduction of antihypertensive medication during the summer. We aimed to investigate the prevalence and details of drug reduction during the summer among outpatients. Among 667 patients, 90 patients (13.5%) had their medication reduced during the summer. The highest rate of drug reduction was for diuretics (17.5%). The patients whose medications were reduced (Group R) took a larger number of drugs and more frequently took diuretics compared with the subjects whose medications were unchanged (N = 559; with no reduction or increase in drugs, Group UC). Moreover, both the office BP and morning home BP of the patients in Group R were significantly lower compared with those of the patients in Group UC. These results suggest that doctors tend to reduce antihypertensive drugs to avoid an excessive decrease in BP especially in patients receiving combination therapy including diuretics.